Exploration of ketone derivatives of succinimide for their antidiabetic potential: In vitro and in vivo approaches - Talib Ayesha; Shah Shafiq Ali; Jan Muhammad Saeed; Ahsan Muhammad Zaeem; Munir Abubakr; Bukhari Ishfaq A.; Sadia Halima; Alomar Taghrid S.; AlMasoud Najla; Rauf Abdur (Green Processing and Synthesis, 2023)
Diabetes mellitus (DM) is one of the most challenging diseases among all the other diseases in the recent era, and it is a life-threatening disorder. The best enzymes to target for treating DM are α-glucosidase and α-amylase. For this purpose, we explored numerous succinimides with ketone functionalities. First, we explored these compounds for their in vitro analysis. Compounds 1 and 4 exhibited excellent inhibition of both enzymes in in vitro studies. These compounds displayed excellent activity with IC50 values of 3.69 and 1.526 µg·mL−1 against the α-glucosidase enzyme. In the α-amylase inhibitory assay, compound 1 has shown excellent potential with an IC50 value of 1.07 µg·mL−1 and compound 4 with an IC50 value of 0.115 µg·mL−1. Based on the in vitro analysis, the potent compounds were further subjected to their in vivo analysis. Before the in vivo analysis, the toxicity profile was checked, and it was confirmed that the compounds were safe at 1,500 µg·kg−1. Then, these compounds were subjected for their in vivo anti-diabetic potential in a mouse model of diabetes. Various concentrations of compounds 1 and 4 were explored by in vivo analysis using glibenclamide as a standard drug. The blood glucose level of the tested and control groups was measured at 0 to 15 days accordingly. Similarly, we also explored compounds 1 and 4 for the oral glucose tolerance test at 0–120 min using glibenclamide as the standard drug. Hence, the succinimide having ketone moiety displayed excellent potential against diabetes.